The advocacy coalitions for the analysis of the accreditation engineering programs in Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2022)
The purpose of this article is to examine the relationships between CFIA-AAPIA and SINAES regarding the quality accreditation of engineering programs in Costa Rica. The study was carried out with the elements present in the framework of promoter coalitions developed by Jenkins and Sabatier (1988) for the analysis of public policies, to determine how the beliefs of the different actors and the coalitions that are formed can affect the content or change of this policy. The main result was how the resources and beliefs of the coalitions that are configured in the implementation of the quality policy in higher education can influence change and can be a limiting factor in its results.
Keywords: accreditation; higher education; advocacy coalitions framework